IMPLEMENTASI E-GOVERNMENT DALAM PERSURATAN DAN ARSIP BIRO UMUM SEKRETARIAT DAERAH PROVINSI RIAU TAHUN 2022-2023 - Nurfadilah ,; Ben Hansel Notatema Zebua (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The General Bureau of the Regional Secretariat of Riau Province has implemented E-Office since 2019; however, the management of correspondence and archives in the Correspondence and Archives Sub-division was still conducted conventionally, as reflected by the increase in paper usage in 2023. This study aims to describe the implementation of E-Government in correspondence and archives management at the General Bureau of the Regional Secretariat of Riau Province in 2022-2023. The study employed a qualitative descriptive approach using the Technology Acceptance Model (TAM) by Fred Davis (1989) as the theoretical framework. Data were collected through semi-structured interviews and documentation, with informants selected using the purposive sampling technique. Data analysis was conducted using the interactive model of Miles and Huberman. The findings indicate that the implementation of E-Government in 2022-2023 had not yet operated optimally. Employees continued to use manual methods such as Excel, logbooks, and physical document storage. The inhibiting factors encompassed technical aspects, including the relatively complex design of the E-Office system and inadequate computer equipment; organizational aspects, including a lack of leadership commitment; and human resource aspects, including resistance from some senior employees to system changes. Future research is recommended to examine other factors influencing E-Government implementation, such as organizational culture, leadership characteristics, and effective archive digitalization strategies. Keywords: E-Government, Correspondence, Archives, Technology Acceptance Model, General Bureau